REFERENCE VOLTAGE GENERATION IN IMAGING SENSORS - HUANG, YING; ROSSI, GIUSEPPE; BLANQUART, LAURENT (2010)
The claimed subject matter provides systems and/or methods that facilitate generating and/or maintaining low noise reference voltages for CMOS imaging System-on-Chip (iSoC) sensors. A primary reference voltage can be generated utilizing a low noise bandgap. Further, the primary reference voltage can be filtered via a low pass filter. The filtered, primary reference voltage can thereafter be distributed to a plurality of isolated domains. Each of the isolated domains can generate an independent set of reference voltages based upon the filtered, primary reference voltage. Moreover, subsets of these reference voltages can be employed by programmable digital to analog converters (DACs). Each of the reference voltages can be isolated from switching noise and/or clock glitches generated within each domain. Further, each DAC output can be buffered to have adequately low impedance with appropriate drive capability and requisite signal swing.